An evaluation of constraints in the adoption of e-commerce model - Mafuka, Alfred (Midlands State University, 2015)
The Internet use is growing at a dramatic pace and is significantly impacting on customer and business market behaviours. As a result, bigger and smaller firms worldwide have started developing and using Internet strategies to enhance competitiveness on the marketplace. However, the evolution of the Internet, and the adoption of a strategic direction focusing on Internet strategies have not been defined on the part of Zimbabwean companies. In this paper, the authors examine the critical constraints in the adoption of the Internet as a business tool. First, a theoretical framework for the Internet as marketing tool is specified. Second, results of the survey that was conducted in order to identify the critical constraints in the adoption of the Internet as a business tool are presented. The research design is purposive. The study found that the adoption of the Internet as a business tool is affected by several factors that include limited financial resources, low computer penetration, lack of technical expertise, limited credit availability and slow service. Finally, propositions are provided for the development and adoption of Internet strategies in Zimbabwe